Penentuan Limbah Mikroplastik Polyethylene Terephthalate (PET) dengan Metoda Glikolisis dalam Air Laut di Kota Padang - Kasma Warni; Indang Dewata (Jurnal Periodic Jurusan Kimia UNP, 2021)
Polyethylene Terephthalate (PET) is a type of plastic waste commonly found in the sea especially disposable soft drink bottles. PET plastic waste can decompose into harmful microplastics if swallowed by marine life. This study aims to determine the microplastic content of PET type in seawater in the city of Padang by glycolysis method using ethylene glycol (EG) solvent with a sodium carbonate as catalyst (Na2CO3) for depolymerization of PET to be a monomer of bis (2-hydroxyethyl terephthalate) (BHET). Glycolysis is carried out for 1 hour at 1960C. In this study, the variation of sodium carbonate (Na2CO3) catalyst mass used are 0.02 gram, 0.04 gram, 0.06 gram, 0.08 gram, and 0.1 gram) and variation of ratio PET bottles: ethylene glycol  (gram: mL) are 10 : 20, 10:30, 10:40 and 10:50. The result obtained is 72.22% BHET product under optimum condition with amount of EG of 30 mL and Na2CO3 catalyst mass of 0.06 grams. The BHET was identified using FTIR to confirm the OH-, C-O, and C = O groups. Seawater samples are taken from three locations namely Padang beach, Tabing beach and Gajah Padang beac. The result shows absence of PET type microplastic in these samples.